Incorporation of Pd nanoparticles on rod and necklace-like SBA-15 supports materials - Lee, S.-P. (Trans Tech Publications Ltd, 2014)
Ion-exchange of palladium (Pd) precursor for two different types of well-ordered SBA- 15 morphologies, necklace-like and rod-like, was studied. Approximately 3.8 wt Pd was successfully incorporated into SBA-15 at pH 10.3. Formation of SBA-15 and Pd/SBA-15 were characterized by Scanning Electron Microscope (SEM), Transmission Electron Microscope (TEM), Thermogravimetry with Simultaneous Difference Thermal Spectroscopy coupled with mass spectrometer (TG/SDTA-MS), Thermogravimetry in combination with Simultaneous Difference Thermal Spectroscopy (TG-SDTA), Inductive Coupled Plasma Mass Spectrometer (ICP-MS) and N2 adsorption-desorption. Reduction of surface area and pore volume of support for Pd/SBA-15 samples may indicate the encapsulation of PdO particles within mesoporous channels of SBA-15. Â© (2014) Trans Tech Publications, Switzerland.